Local wisdom of the Baduy people in managing the forest environment - Setiawan, Eko Adhy; Widjaja, Hinijati (Global Education Journal, 2025)
In rural areas of Indonesia, such as Nagari Batagak, West Sumatra, limited access to health services emphasizes the need for promotive and preventive interventions. The program aims to increase awareness of regular health check-ups and the prevention of degenerative diseases. The program method was implemented on June 16, 2025, involving 35 elderly people aged 60–80 years in Jorong Sawah Liek, Nagari Batagak, Agam Regency, West Sumatra. Activities included basic health checks (blood pressure, blood sugar, Body Mass Index, mid-upper arm circumference), nutritional screening (MNA), sarcopenia screening (SARC-F and handgrip strength), and cognitive screening (MMSE). Health education was provided on healthy aging, nutrition, rational drug use, and sarcopenia prevention. Data analysis was conducted using frequency distribution, univariate, and bivariate analyses. The results showed that the majority of participants were aged 60–70 years (71.4%) and female (82.9%). Obesity was not significantly associated with blood pressure, blood sugar, cholesterol, or uric acid levels. However, older adults without obesity remain at risk for hypertension, diabetes, hypercholesterolemia, and hyperuricemia. Handgrip strength testing showed that 56% of participants experienced muscle weakness, with a slightly higher prevalence in men (60%) than in women (55%). These findings indicate a high risk of sarcopenia, which increases susceptibility to mobility limitations and the risk of falls. Therefore, community-based health screening and education are important regardless of obesity status.